Optimization of Intrinsic ZnO Thickness in Cu(In,Ga)Se(2)-Based Thin Film Solar Cells - Alhammadi, Salh (Materials (Basel), 2019)
The typical structure of high efficiency Cu(InGa)Se(2) (CIGS)-based thin film solar cells is substrate/Mo/CIGS/CdS/i-ZnO/ZnO:Al(AZO) where the sun light comes through the transparent conducting oxide (i.e., i-ZnO/AZO) side. In this study, the thickness of an intrinsic zinc oxide (i-ZnO) layer was optimized by considering the surface roughness of CIGS light absorbers. The i-ZnO layers with different thicknesses from 30 to 170 nm were deposited via sputtering. The optical properties, microstructures, and morphologies of the i-ZnO thin films with different thicknesses were characterized, and their effects on the CIGS solar cell device properties were explored. Two types of CIGS absorbers prepared by three-stage co-evaporation and two-step sulfurization after the selenization (SAS) processes showed a difference in the preferred crystal orientation, morphology, and surface roughness. During the subsequent post-processing for the fabrication of the glass/Mo/CIGS/CdS/i-ZnO/AZO device, the change in the i-ZnO thickness influenced the performance of the CIGS devices. For the three-stage co-evaporated CIGS cell, the increase in the thickness of the i-ZnO layer from 30 to 90 nm improved the shunt resistance (R(SH)), open circuit voltage, and fill factor (FF), as well as the conversion efficiency (10.1% to 11.8%). A further increas of the i-ZnO thickness to 170 nm, deteriorated the device performance parameters, which suggests that 90 nm is close to the optimum thickness of i-ZnO. Conversely, the device with a two-step SAS processed CIGS absorber showed smaller values of the overall R(SH) (130–371 Ω cm(2)) than that of the device with a three-stage co-evaporated CIGS absorber (530–1127 Ω cm(2)) ranging from 30 nm to 170 nm of i-ZnO thickness. Therefore, the value of the shunt resistance was monotonically increased with the i-ZnO thickness ranging from 30 to 170 nm, which improved the FF and conversion efficiency (6.96% to 8.87%).